Mineralogy, petrology and petrogenesis of syenitic rocks of the Porcupine-Destor fault zone near Matheson, Ontario - Pigeon, Luc (University of Ottawa (Canada), 2003)
The mineralogy, petrology and petrogenesis of a representative suite of late Archean syenitic intrusions emplaced along the Porcupine-Destor fault zone near Matheson, Ontario in the southern Abitibi greenstone belt are studied using a combined approach involving field work, petrography, mineral chemistry and, major and trace element geochemistry. Members of the Matheson suite are from east to west: Iris, Garrison, Emens, Ludgate and Pangea intrusions. The Iris, Emens, Ludgate and Pangea intrusions are mostly composed of syenitic rocks with compositions ranging from alkali-feldspar quartz-syenite to melasyenite. Textures range from equigranular to porphyritic. Iris and Pangea intrusions also contain related mafic rocks. The Garrison intrusion is composed of hornblende quartz-monzonite. All intrusions but one have hypersolvus feldspar assemblages; the exception being Garrison intrusion, which displays a subsolvus feldspar assemblage. The occurrence of late aegirine-augite, magnesioriebeckite and widespread albite replacement, especially in rocks from Ludgate and Iris intrusions, indicates that late or post-magmatic sodium-rich fluids variably affected the rocks. Two magmatic series were identified based on silica-saturation properties and alkali-contents. (Abstract shortened by UMI.)
Keywords: Geology.; Mineralogy.